CORRUPTION, INCOME INEQUALITY and ECONOMIC GROWTH: THE FRAGILE FIVE COUNTRİES (1995-2019) (Third Sector Social Economic Review, 2023)
Economic growth is among the priority macro-economic targets for countries. It is known that there are social and economic factors that both affect and are affected by economic growth. Determining the factors affecting economic growth is considered important for countries to follow a stable economic growth and development trend. In this study, the effects of corruption and income inequality, which are thought to affect economic growth, on economic growth were empirically examined in the sample of Fragile Five countries for the period 1995-2019. Within the scope of the analysis using panel data analysis method, the corruption index was used to represent the corruption variable, the gini coefficient to represent the income inequality, and the real gross national product per capita to represent the economic growth. As the results of this study, it was concluded that the increase in the corruption index negatively affects the economic growth in Mexico and the increase in income inequality positively affected economic growth in India, Mexico and South Africa. While the increase in gross fixed capital formation, the control variable of the research model, positively affects economic growth in Brazil and South Africa; In India, on the other hand, it negatively affects economic growth.
Keywords: Corruption; Income Inequality; Economic Growth; Fragile Five; Panel Data Analysis